PREPARATION OF PEARL CALCIUM ALGINATE WITH MAGNETIC PROPERTIES AND THEIR APPLICATION IN THE ADSORPTION OF Cu (ll) - Tapia H., N. (2009)
It has been obtained bead of calcium alginate wit micro-particles of magnetite. The optimum pH for adsorption of Cu (II) lie between 4,5 and 5. From the study of the kinetic of adsorption was determined that the thermodynamic equilibrium was reached after 200 min. The adsorption data fitted well with the Langmuir model and showed the maximum adsorption capacity q(max)= 57,47 mg/g and b = 0,0784.